UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP SISWA KELAS VIII MTS. AL-ILHAMIYAH SIDOMULYO MENGGUNAKAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) PADA SUB MATERI POKOK KUBUS DAN BALOK TAHUN AJARAN 2016/2017 - Mara Samin Lubis (State Islamic University of North Sumatra, 2017)
The type of research used is Classroom Action Research using Realistic Mathematics Education (RME) approach. This classroom action research is conducted through 2 cycles that include planning, implementation, observation and reflection activities. And to know the ability of understanding students' mathematical concepts Researchers use the comprehension test of the concept of mathematics individually. Subjects in this study were students of grade VIII-1 MTs. Al-Ilhamiyah Sidomulyo with a total of 31 students. The result of the research shows that before the giving of action only 3 students from 31 students complete in comprehension test of mathematics concept with percentage of 9.68%. After giving the action in cycle I, the students' understanding of mathematical concepts has increased by 48.39% percentage, or as many as 15 students from 31 students have completed in the comprehension ability test of mathematical concepts. After the improvement of cycle I to cycle II, the result of the ability to understand the concept of mathematics students cycle II has reached the classical completeness with the percentage of 87.10% or as many as 27 students have been completed in the ability to comprehend the concept of mathematics test. From the result of this class action research, the researcher concludes that there is improvement of students' mathematical concept comprehension ability by applying Realistic Mathematics Education (RME) approach to the students of grade VIII-1 MTs. Al-Ilhamiyah Sidomulyo.